The Effect of Value Congruity, Customer Brand Identification, Affective Brand Commitment, Customer Brand Engagement on Coffee Store Brand Loyalty: The Case of Starbucks - Cyntia Jovina Wibowo; Pauline H Pattyranie (Enrichment : Journal of Management, 2021)
Along with the high growth of the coffee shop business in Indonesia, the competition in the coffee shop industry is also getting higher. This makes it difficult for brands to increase the number of customers from the existing market. This is also a challenge for Starbucks because Starbucks currently has competitors in the form of local brands that have lower selling prices than Starbucks. It is important for Starbucks to increase customer loyalty in the midst of this competition. There are various factors that can affect consumer loyalty, namely Value Congruity, Customer Brand Identification, Affective Brand Commitment, and Customer Brand Engagement. The study looked at the influence of these factors on loyalty to the hospitality industry in India. In this research, Data was collected by distributing questionnaires distributed online, containing 32 questions with a Likert scale of 1 – 7. The data were analyzed using the PLS-based SEM method. The results of this study indicate that value congruity has a positive influence on customer brand identification, affective brand commitment and customer brand engagement. Customer brand identification and customer brand engagement also have a positive influence on brand loyalty. While affective brand commitment does not have a significant effect on brand loyalty.